Penerapan Sanksi Pidana Adat Terhadap Pelaku Zina Di Wilayah Kabupaten Padang Lawas Utara - Rahmat Syaputra; Madiasa Ablisar; Agusmidah Agusmidah; Marlina Marlina (Universitas Sumatera Utara, 2019)
Abstract. The implementation of the principle of legality in national criminal law, namely customary criminal law still remains to reveal its figure and existence as a law that lives in society (the living law). The rules of customary criminal law in some areas are still followed and adhered to by their indigenous peoples. Violation of the rules of customary criminal law is still seen as something that can cause shock and disturb the cosmic balance of the community, for the offender will be given customary reaction in the form of customary sanctions by the community.The purpose of this study is to examine and analyze legally how to regulate customary crimes for adulterers in North Padang Lawas Regency; to know and analyze legally the application of customary criminal sanctions against perpetrators of adultery in the North Padang Lawas Regency; To examine the authority of adat leaders in completing zina criminal acts in the North Padang Lawas Regency. This type of research is empirical legal research with data collection techniques for interviews with traditional leaders and elders in North Padang Lawas district.Customary criminal law regulation in North Padang Lawas Regency against customary sanctions against zina criminal acts in North Padang Lawas district is a social act committed by a person or group of men between men and women outside of marital ties that violate moral norms, then the act is deemed as an act of adultery according to customary law in North Padang Lawas Regency. Associations that violate the norms of normalization referred to in customary law in North Padang Lawas Regency are social norms for men and women that have been implied in customary law. in the form of Sappal Dila, a type of punishment that requires the perpetrator to cut a goat or buffalo / ox by inviting a person to eat a village to make an apology. The application of customary criminal sanctions against the perpetrators of adultery in North Padang Lawas Regency was imposed by the customary chief, Raja Panusunan Bulung and Raja Pamusuk after holding a traditional meeting attended by Mr. Namalim (religious figure), Datu (health physician), Pangatak-pangetong / rokkaya (the host as well as the clerk), Panyujukon burangir (carrier of betel leaf), Halak na di Huta (community in the village) as well as witnesses who have been prepared;Authority of customary leaders in completing criminal acts of adultery in North Padang Lawas Regency, namely based on the provisions of Article 5 paragraph (3) of Law Number 1 of 1951 concerning Temporary Measures to Organize Unity in the Structure of Civil Judiciary and Procedure is the basis of the authority of the elders adat in addressing customary crimes against perpetrators of the zone in North Padang Lawas Regency. Keywords: indigenous criminal sanctions, criminal acts, adultery